Book Review T. Rothengatter & R.D. Huguenin (Eds.) Traffic and transport psychology: Theory and applications. Amsterdam, Elsevier - Gärling, Tommy (European Journal of Transport and Infrastructure Research, 2006)
The book is the selected proceedings of the second international conference of traffic and transport psychology (TTP) held in Bern, Switzerland, in 2000. The first conference took place 1996 in Valencia, Spain, the third 2004 in Nottingham, UK (Rothengatter & CarbobellVaja, 1997; Underwood, 2005). A casual look at the three volumes from the conferences indicates that their structure and contents are similar. In the volume under review, keynote lectures, selected papers and poster presentations are included. A first part contains an introduction by the editors and three chapters addressing the general issue of theory in a field of applied research such as TTP. The remaining parts are dominated by reported empirical studies with some interspersed overview, conceptual, or discussion chapters. Truthfully representing current TTP research, these include road user characteristics (cognition and performance, social and differential psychology, and impairment), road safety (driver information and support systems, enforcement and training, and selection and rehabilitation), and mobility and the environment